Facile production of mesoporous WO3-rGO hybrids for high-performance supercapacitor electrodes: an experimental and computational study - Samal, Rutuparna; Chakraborty, Brahmananda; Saxena, Manav; Late, Dattatray J.; Rout, Chandra Sekhar (ACS Sustainable Chemistry & Engineering, 2019)
This work explored a promising supercapacitor electrode material (WO3-rGO hybrids) synthesized via a simplistic one-pot hydrothermal synthesis route. Various analytical studies (X-ray diffraction study, Raman spectroscopy, field emission scanning electron microscopy, transmission electron microscopy, X-ray photoelectron spectroscopy, Brunauer-Emmett-Teller analysis) were employed in furtherance to explore the structural, morphological, compositional, and surface areal properties of the prepared materials. The enhancement in electrochemical supercapacitive properties were evaluated from pure hexagonal phase WO3 to the various hybrids, depending on the concentration of GO introduced into it, using cyclic voltammetry, galvanostatic charge/discharge, and electrochemical impedance spectroscopy. The WG-80 composite revealed the high rise in capacitance value of 801.6 F/g overcoming the individual capacitance of rGO (71.11 F/g) and WO3 (94.22 F/g) at a current density of 4 A/g with good cycling stability (75.7%) over 5000 cycles. We have presented quantum capacitance from ab initio calculations and provided theoretical explanation from the orbital interactions.
Keywords: Density functional theory; Hydrothermal method; supercapacitor; WO3-rGO hybrids